Should Independent Board Members with Social Ties to Management Disqualify Themselves from Serving on the Board? - Hoitash, Udi (2011)
This paper examines whether independent directors who have social ties to management (inside directors) can effectively perform their fiduciary duty to monitor management on behalf of shareholders. Ex ante, it is not clear whether social ties will enhance or obstruct the quality of board performance. Theory suggests that directors who are socially tied to management are ineffective and would make decisions favoring management. However, social ties can increase trust and information sharing between management and independent directors, improving directors’ ability and effectiveness in governing the company (Westphal, J.D.: 1999, The Academy of Management Journal 42(1), 7–24). To examine these contradicting predictions I use social network analysis and construct proxies for social ties between management and independent board members. Using these proxies, I first demonstrate that social ties are associated with higher managerial compensation. Further analyses reveal that these results are driven by social ties that include members of the compensation committee. Conversely, I demonstrate that financial reporting quality is improved when social ties exist. Specifically, I find that the likelihood of material weaknesses in internal controls and the likelihood of financial restatements are lower in companies with social ties. I further observe that this improved quality of financial reporting holds only when social ties include members of the audit committee. I conclude that ethically, socially tied independent directors should disqualify themselves from serving on compensation committees where social independence is essential. However, in tasks where collaboration with management is essential, directors with social links to each other can be of added value to shareholders.
Keywords: Social ties; Social Network; Independent directors; financial reporting quality; Corporate Governance; CEO compensation